Figure animation via bone method / Mas Ayu Husna Mohamad - Mohamad, Mas Ayu Husna (2012)
This research paper present about method for animated the character animation. Character animation brings a static model to life by defining how its geometry changes over time. Character animation is quite different from other forms of animation (even facial animation) because of the underlying skeletal structure - motions are characterized more by rotations than by linear motion. Animators typically animate the bones of a character, either directly, or indirectly using inverse kinematics. The skin follows the bones, deforming as necessary to produce smooth transitions at joints. There are many ways to animate characters, including skeletal (bone-driven) animation, shape interpolation, spatial deformation, physically-based deformation and direct animation of vertices or spline-control points. Animation of any kind also introduces new challenges when combined with other areas of computer graphics, particularly areas that have traditionally considered only static scenes. Bone based animation is a good way to add believable animation to your engine without the overhead of vertex animation (morph targets).